Web-Based Turkish Dichotic Listening Test-Retest Reliability - Öykü Akkay; Emre Eskicioğlu (Hacettepe University Faculty of Health Sciences Journal, 2026)
Objective: This study evaluated the test–retest reliability of a newly developed web-based dichotic listening test with Turkish syllables presented to individuals with normal hearing. By adapting the dichotic listening paradigm from its traditional laboratory implementation to a digital format, this study aimed to increase accessibility. Materials and Methods: Forty-seven participants aged between 18 and 35 with normal hearing completed a web-based Turkish dichotic listening test. Participants were recruited online and completed the test using their own devices and headphones. A retest session was conducted two weeks after the first test. Results: The test exhibited high test-retest reliability across both ears in the non-forced condition (ICC_right = .79; ICC_left = .80), moderate reliability in the forced right condition (ICC = .70), and notably lower reliability in the forced left condition (ICC = .40).Conclusion: The findings indicate that the DL test provides high reliability under non-forced conditions, but its reliability decreases under attentional conditions.